2021
DOI: 10.2478/adms-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Flame Spraying Coatings Reinforced with Particles of Carbon Nanotubes

Abstract: The article presents the results of the preliminary research of tribological properties of flame sprayed nickel and aluminum coatings reinforced with carbon nanotubes made on the structural steel S235J0 substrate. The carbon material – carbon nanotubes Nanocyl NC 7000 (0.5 wt.% and 1 wt.%) was used for structural reinforcement. The properties evaluation was made by the use of optical microscopy, scanning electron microscopy, Raman spectroscopy, microhardness measurements, and by means of abrasion and erosion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These types of tubular walls are used for the production of heat exchangers in waste incineration boilers. Thermally sprayed coatings with nickel-based alloys significantly increase the resistance of pipes to corrosion and erosion [ 33 , 34 , 35 ]. They can be manufactured on new tubular structures or in the event of the need to repair elements of a panel damaged during operation.…”
Section: Resultsmentioning
confidence: 99%
“…These types of tubular walls are used for the production of heat exchangers in waste incineration boilers. Thermally sprayed coatings with nickel-based alloys significantly increase the resistance of pipes to corrosion and erosion [ 33 , 34 , 35 ]. They can be manufactured on new tubular structures or in the event of the need to repair elements of a panel damaged during operation.…”
Section: Resultsmentioning
confidence: 99%
“…The abrasive wear tests were performed according to ASTM G65 standard [13]. A 5kg load was used to push the sample against the rotating rubber lined wheel rotating at 200rpm, the sand was fed between the sample and the rotating wheel as shown in Figure 3.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…The laser surface alloying process in comparison to laser melting allows for a wider influence on the structure and properties of surface layers by adjusting the chemical composition of a liquid metal pool by the addition of the alloying elements. Previous studies in this field have shown that the addition of elements with high affinity to carbon in the laser alloying process may result in the formation of an in situ composite structure in the surface layer area [16][17][18][19]. An example of such an element is titanium, which when added in the laser alloying of a ductile cast iron surface causes the formation of high-hardness titanium carbides in the structure of the surface layer, which has a beneficial effect on the wear resistance of the surface.…”
Section: Introductionmentioning
confidence: 99%